Are all fibrinogen concentrates the same? The effects of two fibrinogen therapies in an afibrinogenemic patient and in a fibrinogen deficient plasma model. A clinical and laboratory case report - Goodarzi, Soutiam; Abu-Hanna, Jeries; Harper, Sarah; Khan, Dalia; Morrow, Gael; Curry, Nicola (Frontiers in Medicine, 2024)
The choice of treatments for inherited, or acquired, fibrinogen deficient states is expanding and there are now several fibrinogen concentrate therapies commercially available. Patients with the rare inherited bleeding disorder, afibrinogenemia, commonly require life-long replacement therapy with fibrinogen concentrate to prevent hemorrhagic complications. Recent reports in the setting of acquired bleeding, namely trauma hemorrhage, have highlighted the potential importance of the different compositions of fibrinogen supplements, including cryoprecipitate and the various plasma- derived concentrates. Clot strength and the subsequent susceptibility of a clot to lysis is highly dependent on the amount of fibrinogen as well as its structural composition, the concentration of pro- and anti-coagulant factors, as well as fibrinolytic regulators, such as factor XIII (FXIII). This report details the effects of two commercially available fibrinogen concentrates (Riastap®, CSL Behring and Fibryga®, Octapharma) on important functional measures of clot formation and lysis in a patient with afibrinogenemia. Our report offers insights into the differential effects of these concentrates, at the clot level, according to the variable constituents of each product, thereby emphasizing that the choice of fibrinogen concentrate can influence the stability of a clot in vivo. Whether this alters clinical efficacy is yet to be understood.